Education and public works during the first Peronism. Building schools in the province of Buenos Aires - Petitti, Eva Mara (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2016)
This article analyzes the Integral Plan for School Construction (Plan Integral de Edificación Escolar- PIEE) approved in the province of Buenos Aires in 1948. We study the legal changes regarding the type of financing and the scope and limits involving its application. We analyzed the governorates of Domingo A. Mercante (1946-1952) and Carlos Aloe (1952-1955). The results show that implementation of the plan, had significantly impacted about the growth in the number of state-owned educational institutions. Moreover this transformation came from a change in the application of resources and the greater involvement of state agencies in planning buildings, related to greater involvement in education which acquired the provincial government during this period.